2008
DOI: 10.2174/138920008783331077
|View full text |Cite
|
Sign up to set email alerts
|

CSF as a Surrogate for Assessing CNS Exposure: An Industrial Perspective

Abstract: For drugs that directly act on targets in the central nervous system (CNS), sufficient drug delivery into the brain is a prerequisite for drug action. Systemically administered drugs can reach CNS by passage across the endothelium of capillary vasculatures, the so-called blood-brain barrier (BBB). Literature data suggest that most marketed CNS drugs have good membrane permeability and relatively high plasma unbound fraction, but are not good P-glycoprotein (P-gp) substrates. Therefore, it is important to use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
137
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 81 publications
(134 reference statements)
4
137
1
Order By: Relevance
“…There are two major pathways to deliver drug to CSF, namely transport from brain to CSF by crossing the ependymal cell monolayers between the brain and CSF interface or transport from blood to CSF by crossing the BCSFB. Most studies have suggested that brain to CSF transport is the major route of drug delivery; therefore, CSF concentration can be used as a surrogate to assess the free drug concentration in brain tissues (Liu et al, 2006(Liu et al, , 2009Lin, 2008). Compared with the knowledge of the effect of Bcrp and Pgp in restricting drug transport across the BBB, little is known about their impact on drug transport across the BCSFB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two major pathways to deliver drug to CSF, namely transport from brain to CSF by crossing the ependymal cell monolayers between the brain and CSF interface or transport from blood to CSF by crossing the BCSFB. Most studies have suggested that brain to CSF transport is the major route of drug delivery; therefore, CSF concentration can be used as a surrogate to assess the free drug concentration in brain tissues (Liu et al, 2006(Liu et al, , 2009Lin, 2008). Compared with the knowledge of the effect of Bcrp and Pgp in restricting drug transport across the BBB, little is known about their impact on drug transport across the BCSFB.…”
Section: Discussionmentioning
confidence: 99%
“…To deliver drugs to the brain, systemically administrated drugs have to pass the BBB and/or the BCSFB. Previous studies have shown that CSF can be used as surrogates to assess free drug concentrations in brain (Liu et al, 2006(Liu et al, , 2009Lin, 2008). The expression of Pgp, but not Bcrp, on the luminal membrane of choroid plexus epithelial cells has been reported (Rao et al, 1999;Daood et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The free drug hypothesis is a well accepted and widely applied concept in drug discovery and development Hammarlund-Udenaes et al, 2008;Lin, 2008;Smith et al, 2010). This hypothesis states that the free (unbound) drug at the site of action exerts pharmacological activity, rather than total drug (bound and unbound), and that the free drug is able to distribute from the systemic circulation across membranes to tissues, rather than total drug.…”
Section: Introductionmentioning
confidence: 99%
“…For neuroscience therapeutic targets, accurate understanding of total and free drug concentrations in plasma and brain, particularly brain interstitial fluid, is critical for developing PK/PD relationships, projecting doses, and designing clinical studies. Several techniques have been developed to obtain free drug concentrations in the brain directly or indirectly Liu et al, 2008;Di and Kerns, 2011), including in vivo microdialysis (direct) (Elmquist and Sawchuk, 1997;Hammarlund-Udenaes et al, 1997;de Lange et al, 1997;Hammarlund-Udenaes, 2000;Watson et al, 2006), CSF sampling (indirect) (Shen et al, 2004;Lin, 2008;Fridén et al, 2009b), and a combination of brain distribution through measuring plasma and brain concentration time courses ) and brain tissue binding (quasi-direct) (Kalvass and Maurer, 2002;Mano et al, 2002;Maurer et al, 2005;Summerfield et al, 2006;Liu et al, 2009). The latter approach of measuring brain distribution and brain tissue binding is one of the most common strategies in the pharmaceutical industry to elucidate total and free drug PK relationships in brain and plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nonhomogeneous drug distribution within the brain, as a result of drug binding to brain tissue and the presence of influx and efflux carrier-mediated transport across the BBB and BCB and brain cell membranes, complicates the prediction of drug concentrations in the brain extracellular fluid (bECF), the site of action for CNS drugs whose targets are in the extracellular space. To address these complexities of CNS drug development, approaches such as positron emission tomography (PET) or single photon emission computed tomography imaging to measure receptor occupancy (RO) (Tauscher and Kapur, 2001) and measurement of drug concentrations in cerebrospinal fluid (CSF) (de Lange and Danhof, 2002;Shen et al, 2004;Lin, 2008) have been used; however, limitations exist preventing consistent application of these approaches. Notable among these limitations is the lack of a suitable tracer ligand to conduct imaging studies and the technical complexities associated with CSF sampling in humans.…”
Section: Introductionmentioning
confidence: 99%